Facial Angiofibroma Severity Index (FASI): reliability assessment of a new tool developed to measure severity and responsiveness to therapy in tuberous sclerosis‐associated facial angiofibroma. (20th August 2014) - Salido‐Vallejo, R.; Ruano, J.; Garnacho‐Saucedo, G.; Godoy‐Gijón, E.; Llorca, D.; Gómez‐Fernández, C.; Moreno‐Giménez, J. C.
Summary Background Tuberous sclerosis complex (TSC) is an autosomal dominant neurocutaneous disorder characterized by the development of multisystem hamartomatous tumours. Topical sirolimus has recently been suggested as a potential treatment for TSC‐associated facial angiofibroma (FA). Aim To validate a reproducible scale created for the assessment of clinical severity and treatment response in these patients. Methods We developed a new tool, the Facial Angiofibroma Severity Index (FASI) to evaluate the grade of erythema and the size and extent of FAs. In total, 30 different photographs of patients with TSC were shown to 56 dermatologists at each evaluation. Three evaluations using the same photographs but in a different random order were performed 1 week apart. Test and retest reliability and interobserver reproducibility were determined. Results There was good agreement between the investigators. Inter‐rater reliability showed strong correlations (> 0.98; range 0.97–0.99) with inter‐rater correlation coefficients (ICCs) for the FASI. The global estimated kappa coefficient for the degree of intra‐rater agreement (test–retest) was 0.94 (range 0.91–0.97). Conclusions The FASI is a valid and reliable tool for measuring the clinical severity of TSC‐associated FAs, which can be applied in clinical practice to evaluate the response to treatment in these patients.